Finite Element Analysis of Miniplate for Post-Fracture Finger Rehabilitation Device - Nanang Qosim; Ratna Monasari; Zakki F. Emzain; Lutfi Hakim; Ali Sai’in (Journal of Applied Engineering and Technological Science (JAETS), 2020)
Miniplate plays an important role as one of the implant components used as a rehabilitation device for a post-fracture finger. In this study, an analysis was carried out to determine the strength of the miniplate design made from Ti-6Al-4V titanium alloy material. Simulation and analysis were carried out using the finite element method. The given input for modeling tensile and bending loads determined von Mises stress, kinetic energy, strain energy, and internal energy. The analysis showed that uneven von Mises stress and strain distribution have occurred. The critical concentration of stresses was located at the center of the miniplate and these values were a lot lower than the yield stress of Ti-6Al-4V.